Defining talent in management science: Does it really matter? - Janowski, Andrzej; Martynyuk, Volodymyr (Publishing House of Wroclaw University of Economics and Business, 2023)
Talent management has a long scientific trajectory of interest both in organizational and academic dimensions. Over the years, the talent concept has evolved, becoming a managerial phenomenon implemented to different sectors, yet, there is a debate in the context of defining talent, with no agreement as to the semantic concept. Moreover, many publications do not even make any effort to define the talent which, however, does not prevent them from proving the existence of various relations between talent management and other economic phenomena – and this does not merely apply to the academia. Both scholars and practitioners face unfettered freedom in the formulation of what elements constitute the term of talent and its meaning, creating the subject literature, some of which vague and biased, and an extensive analysis of contemporary contribution is lacking. As a consequence, ‘talent’ has become whatever the researcher or practitioner established it to be, creating a path towards scientific chaos. To address this gap, the author proposed an SLR and bibliometrics study of 235 articles published in 71, IF-ranked management journals, from January 1966 to July 2021. There are three objectives of this paper: to analyse definitions of talent aiming at their clarity and unambiguity, to identify trends, and to estimate the future research directions in this area. Finally, as the first attempt of this kind in the domain of science to determine whether there is a need for defining talent to achieve the research goals. As such, this is a new perspective on the existing state of knowledge and it meets the aim and scope of Argumenta Oeconomica.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 287-307
Keywords: competency; effectiveness; performance; personality; talent